LEGAL PROTECTION AND LIABILITY OF THE BUSINESS ACTORS AGAINST TOURISTS IN MT. AGUNG BALI - Putra, I Ketut Wira Cipta; Astara, I Wayan Wesna; Arjaya, I Made (YURIS: Journal of Court and Justice, 2024)
Incidents of accidents during risky climbs have been reported in Bali, and yet to date there are no specific legal regulations regarding mountaineering tourism in the region. Mountaineering tourism is a type of tourism with a high risk, making it very important to implement legal regulations that can provide protection to tourists in any undesirable situation. This research aims to evaluate the legal protection of tourists according to Law No. 10/2009 on Tourism as well as the liability of mountain climbing tourism business actors to those who have experienced losses. This is a qualitative research which adopted normative and conceptual approach. The research findings indicate that there is a necessity for additional regulations as stated in the Governor Regulation of Bali No. 52/2021 concerning Regulations for the Implementation of Regional Regulation No. 5/2020 concerning Standards for the Implementation of Balinese Cultural Tourism. In accordance with Article 1366 of the Civil Code, businesses or managers of the mountain climbing tourist attractions in Bali are obliged to be responsible in the case of accidents that have caused significant losses to tourists. The liability of business actors can also refer to Article 7 of Law No. 8/1999 on Consumer Protection. In addition, the liability of business actors as managers of tourist attractions is also referred to Article 26 of Law No. 10/2009 concerning Tourism and Article 6 No. 3 of Bali Province Regional Regulation No. 5/2020 concerning Standards for the Implementation of Balinese Cultural Tourism.